Colorimetry analysis of coat color and its relationship with fiber traits in alpacas - Cruz A. (2021)
This research was partially funded by CONCYTEC-FONDECYT under the call for proposals E038-01 with contract number: 029-2019-FONDECYT-BM-INC.INV. BOKU- University of Natural Resources and Life Sciences, Vienna kindly provided the chromameter.